Efficacy and safety of rivaroxaban compared to enoxaparin in treatment of cancer‐associated venous thromboembolism. (12th June 2018) - Simmons, Benjamin; Wysokinski, Waldemar; Saadiq, Rayya A.; Bott‐Kitslaar, Dalene; Henkin, Stanislav; Casanegra, Ana; Lenz, Charles; Daniels, Paul; Bjarnason, Haraldur; Vargas, Emily; Hodge, David; Holton, Sara J.; et al.
Abstract: Background: Low molecular weight heparin (LMWH) is the guideline‐endorsed treatment for cancer‐associated venous thromboembolism (cVTE). Study objectives were to compare the efficacy and safety of rivaroxaban and enoxaparin in cVTE. Methods: Using a cohort study design, consecutive patients with cVTE (3/1/2013‐7/31/2016), enrolled in the Mayo Thrombophilia Clinic Direct Oral Anticoagulants Registry, were compared to contemporary cancer patients receiving enoxaparin. The cumulative incidence of venous thromboembolism (VTE) recurrence, major and clinically relevant non‐major bleeding, and survival were assessed at 3 and 12 months. Results: Ninety‐eight patients received rivaroxaban (51% female, mean age 63 ± 12 years) and 168 enoxaparin (34.5% female, mean age 62 ± 15 years). The most common cancers included gastrointestinal/pancreatic, genitourinary and hematologic cancers. More than half of patients had pulmonary emboli at presentation. More than half had metastases, and two‐thirds were receiving chemotherapy. At 3 months, there were no differences in VTE recurrence (rivaroxaban 1.0% vs enoxaparin 4.2%; P = .15), major bleeding (rivaroxaban 5.1% vs enoxaparin 3.6%; P = .55), or all‐cause mortality (rivaroxaban 4.1% vs enoxaparin 8.9%; P = .14). At 12 months, these outcomes did not differ by treatment strategy. Conclusion: The results of this "real‐world" experience with cVTE suggest that rivaroxaban may offer a safe and effective alternative to LMWH.